HEC-HMS Based Hydrological Modeling for Assessing Reservoir Impacts on Flood Hydrographs in the Pacal Watershed - Yuliani Wahyu Sardana (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The Pacal Watershed in Bojonegoro Regency faces severe periodic flooding driven by intense tropical rainfall and land-use change, making the modeling of how the integration of the Pacal and Gongseng reservoirs attenuates flood hydrographs in small tropical catchments a critical issue. This study introduces a novel framework modeling hydrograph transformations resulting from the interaction between the historical Pacal Reservoir and the modern Gongseng Reservoir using HEC-HMS employing the SCS Curve Number loss method and Nakayasu SUH transformation achieving high predictive reliability with a Nash-Sutcliffe Efficiency score of NSE = 0,81. Simulation results demonstrate that dual-reservoir integration significantly mitigates downstream flood risks across 100-year to 1,000-year return periods, achieving peak discharge reductions of 55,46% to 59,38% (320,9 m3/s to 379,6 m3/s) and delaying peak arrival times by 2 to 6 hours with Pacal Reservoir attenuating 163,1 m3/s – 195,3 m3/s and Gongseng Reservoir reducing 107,2 m3/s – 115,6 m3/s. This study proves that the reservoirs function as reliable hydraulic shock absorbers that extend the emergency evacuation lead-time window for vulnerable downstream communities. Furthermore, it reveals a storage efficiency decay phenomenon during extreme storm events due to finite surcharge storage capacity, underscoring the necessity of pre-release operational rule curves despite modeling limitations that omit sedimentation, baseflow, and channel routing.